Implementation research to scale up the women and infants integrated interventions for growth study (WINGS) in Himachal Pradesh: Protocol for a quasi-experimental, mixed-methods study - Arun Singh Jadaun; Jaideep Kumar; Barsha Gadapani Pathak; Sudha Devi; Pradeep Kumar Thakur; Gopal Beri; Mohan Dutt; Seema Thakur; Sanjiv Kumar Verma; Sanjay Mankotia; Anjali Chauhan; Ravinder Kumar; et al. (PLoS ONE, 2026)
Background Maternal undernutrition, anaemia, low birthweight (LBW) and childhood stunting remain major public health challenges in India. Evidence from the Women and Infants Integrated Growth Study (WINGS) randomised controlled trial in Delhi showed that an integrated package of health, nutrition, psychosocial and water, sanitation and hygiene (WaSH) interventions delivered from preconception through early childhood substantially reduced LBW and stunting. However, national programmes largely emphasise pregnancy and early childhood, with limited attention to preconception care, and there is little evidence on government-led scale-up models. This protocol describes government-led implementation research to scale up WINGS in Himachal Pradesh. Methods We will conduct a 36-month mixed-methods study using implementation science principles and a theory-driven process evaluation. Implementation will begin in a learning block, followed by expansion to remaining blocks. The design is anchored in the Consolidated Framework for Implementation Research (CFIR), RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) and COM-B (Capability, Opportunity, Motivation → Behaviour). Evaluation will use an Interrupted Time Series (ITS) design. Participants include preconception women, pregnant women, postpartum mothers, children under 24 months, frontline workers (ASHAs, AWWs, ANMs) and facility staff. Interventions span health, nutrition, psychosocial and WaSH domains, integrated within ICDS and National Health Mission platforms. The objective is to develop an optimised model for scale-up that is sustainable, scalable and achieves high-quality population coverage. Outcomes include anaemia, low BMI and inadequate weight gain among women and children, with process indicators assessing compliance. Quantitative data will be analysed using segmented regression in R; qualitative data will undergo framework analysis; and economic evaluation will estimate incremental cost-effectiveness (S4 File: costing forms). Discussion This implementation research will generate evidence on the feasibility and scalability of integrating preconception-to-early-childhood interventions within government systems to inform national policy. Registration CTRI/2023/10/058538 (Registered on 11/10/2023).